Severe Bordetella pertussis infection and vaccine issue in Chongqing, from 2012 to 2018. (July 2019) - Liu, Zhidai; Liu, Shan; Shu, Yi; Yang, Zuqun; Peng, Bin; Xu, Hongmei; Li, Qubei; Luo, Zhengxiu; Dai, Jihong; Liu, Enmei; Fu, Zhou; Zou, Lin
Highlights: Infants younger than 12 months had the greatest burden of pertussis in Chongqing. The incidence of pertussis in Chongqing appeared to be a periodic pattern, high in summer and low in winter. The problem of quality of vaccine against pertussis in China may begin in 2014, which was more serious than was reported. Simultaneous amplification and testing could be a potential assay for measuring Bordetella pertussis infection in the future. Abstract: Objective: Pertussis is a highly contagious respiratory illness mainly caused by the Gram-negative bacterium Bordetella pertussis . The infection of B. pertussis has been increasing and the current diagnosis of pertussis in children is challenging; little is known of B. pertussis infection in Chongqing. Methods: There were 25, 441 children (14, 863 male and 10, 578 female) with suspected pertussis enrolled in our retrospective study from December 2012 to November 2018. Then 800 children with suspected B. pertussis infection were randomly chosen to be evaluated by simultaneous amplification and testing in this prospective study. Results: Infants younger than 12 months had the greatest burden of pertussis, and the incidence of pertussis in Chongqing appeared to have a periodic pattern. The problem of vaccine quality in China was more serious than previously reported based on the fluctuation of infection rates from 2012 to 2018. Simultaneous amplification and testing to detect B. pertussis RNA (Area Under Curve: 0.900 and Kappa value: 0.831) had better diagnostic performance than real-time PCR for B. pertussis DNA (Area Under Curve: 0.869 and Kappa value: 0.690). Conclusions: We revealed the characteristics of B. pertussis infection and vaccine issues in Chongqing. Simultaneous amplification and testing could be a potential novel assay for measuring B. pertussis infection in the future.